Optimisasi PID pada Sistem Mesin Tunggal Terpasang STATCOM dengan Algoritme Flower Pollination - Avrin Nur Widiastuti; Suseto Mahardiko; Sasongko Pramono Hadi (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2016)
Indonesia as a big country is facing electricity demand increase as the economy is intensively growing. Along with the economy growth, the electricity demand is also increasing. This should be balanced with the growth of power plants installed, but power plants can not be built in a short time. This growth may affect the stability. Stability is one of main problems of power system. Power system can be represented by simplifying it into Single Machine Infinite Bus (SMIB). Flexible AC Transmission System (FACTS) is one of the solutions to enlarge the capacity by compensating the reactive load. By installing the FACTS, the dynamic characteristic of power system also changes. The result shows that system has better dynamic response with FACTS than without FACTS. A proper control is subsequently needed for tackling those phenomenons, e.g. using PID-POD controller. In this type of controller, the PID constant is needed to be determined. Flower Pollination Algorithm (FPA) is then employed for solving such problem. As the newest metaheuristic method, FPA has shown better characteristic than other methods. The results show that FPA can be used as a method to find the optimal PID controller constant in a simple power sytem, such as SMIB.